Illness Cognitions Among Adolescents and Young Adults Who Have a Parent with Cancer: a Qualitative Exploration Using the Common-Sense Model of Self-regulation as a Framework. - Fletcher, Chloe; Wilson, Carlene; Flight, Ingrid; Gunn, Kate; Patterson, Pandora (International Journal of Behavioral Medicine, 2019)
Background: Individuals construct beliefs about an illness based on their own perceptions, interpretation, and understanding of the illness and its treatment. These beliefs (collectively referred to as "illness cognitions" or "representations") can have implications for psychological outcomes in family members and carers of an individual with an illness. The aim of this study was to explore young people's perceptions of their parent's cancer using the Common-Sense Model of Self-Regulation as a theoretical framework. Methods: Semi-structured, one-on-one interviews were conducted with young people who had a parent diagnosed with cancer. Interview transcripts were analysed using deductive thematic analysis techniques. Results: Eleven young people aged 15–24 years participated in the study. Major themes aligned with the dimensions of the Common-Sense Model of Self-Regulation. Young people described their experiences with parental cancer with reference to cognitive representations (beliefs about the illness identity, their understanding or coherence of the illness, and consequences, curability or controllability, timeline, and cause of the illness) and emotional representations (emotional beliefs and subjective feelings about the illness). Conclusions: Findings indicate that young people's perceptions of their parent's cancer can be usefully described within the framework of the Common-Sense Model of Self-Regulation. Future research should investigate the relationships between young people's illness cognitions, coping strategies, and psychological adjustment following their parent's cancer diagnosis. This will provide valuable insights for the development of interventions that target specific types of illness cognitions associated with maladaptive coping strategies and poor adjustment.